2018
DOI: 10.3390/ijerph15061207
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Inverse Associations of Obesity and Fat Accumulation Indicators with Testosterone in Non-Diabetic Aging Men

Abstract: Introduction/Objective: The aim of the study was to show which of the adipose tissue accumulation indicators correlate with testosterone disorders in non-diabetic aging men. Material and methods: 455 non diabetic men, recruited at primary care facilities, aged 50–75 participated in the study. The participants underwent anthropometric measurement and ELISA determination of total testosterone (TT), estradiol (E2), dehydroepiandrosterone sulphate (DHEA-S), sex hormone binding protein (SHBG), and the determination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 34 publications
(36 reference statements)
3
24
0
Order By: Relevance
“…Associations of GRS with obesity-related traits in the present study were not identified in either elderly men or elderly women, suggesting that genetic factors had a very little contribution in the elderly population. Numerous studies have indicated that hormonal factors contribute to obesity in the elderly, with the decline in testosterone being associated with an increased risk for obesity in aging men [46]. In women, aging is associated with a decline in estrogen, which is known to protect against weight gain by increasing energy expenditure.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Associations of GRS with obesity-related traits in the present study were not identified in either elderly men or elderly women, suggesting that genetic factors had a very little contribution in the elderly population. Numerous studies have indicated that hormonal factors contribute to obesity in the elderly, with the decline in testosterone being associated with an increased risk for obesity in aging men [46]. In women, aging is associated with a decline in estrogen, which is known to protect against weight gain by increasing energy expenditure.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Although aging men do not experience a menopause-like dramatic decrease in sex hormone levels as experienced by women, testosterone levels decline steadily with age in men [34]. These declining testosterone levels are associated with elevated visceral adiposity observed in aging men [35], which may play a role in increased cardiovascular risk in aging men. Testosterone therapy has been shown to increase muscle mass/decrease fat mass in older men [36, 37]; therefore, long-term therapy may improve metabolic health by improving lean/fat mass ratio.…”
Section: Main Textmentioning
confidence: 99%
“…High serum testosterone is associated with reduced subcutaneous and increased abdominal adiposity in women, while low testosterone is associated with the same effect in men [25][26][27]. In older men, sex hormone levels do not decrease as rapidly as in menopausal women however, testosterone levels decline steadily with age [28].These declining testosterone levels have been reported to be associated with elevated visceral adiposity in older men [29]. This may play a role in increased risk of cardiovascular diseases in aging men.…”
Section: Discussionmentioning
confidence: 98%